Field comparison of inhalable air samplers for the determination of occupational exposure to inhalable aerosols and soluble proteins in food production. - Darbakk, Christine; Graff, Pål; Olsen, Raymond (Journal of Occupational & Environmental Hygiene, 2025)
This study assessed the performance of the Institute of Occupational Medicine (IOM) and Gesamtstaubprobenahme (GSP) personal inhalable aerosol samplers in measuring aerosol and soluble protein (SP) concentrations across 12 food industry environments. A total of 193 sampling pairs (GSP and IOM) were analyzed for inhalable aerosols, and 185 sampling pairs for SP. Median aerosol concentrations ranged from 0.2 mg/m³ in snacks, nuts, and chips production to 5.6 mg/m³ in spreads production. The IOM sample had a median aerosol concentration of 1.8 mg/m³, while the GSP had a slightly lower median of 1.4 mg/m³, generally collecting 17% less inhalable aerosol than the IOM in most environments. The IOM also included wall deposits in its gravimetric determinations, contributing an additional 10–30% to the overall aerosol concentrations. For SP concentrations, the IOM measured higher aerosol concentrations in environments with a particle size distribution dominated by larger particles, while the GSP showed higher SP concentrations in environments dominated by smaller, respirable particles. The Tobit mixed-effect models showed that the IOM had statistically significantly higher aerosol concentrations compared to the GSP, but significantly lower SP concentrations than the GSP. However, these differences between the samplers were relatively small, suggesting that in occupational hygiene practices, both samplers can be used.